Mycobial deterioration in strychnine and brucine of Strychnos nux-vomica seeds - A. K. ROY, G. R. DUTTA and (Indian Phytopathology, 2002)
Two major indolic alkaloids, viz., strychnine (0.87%) and brucine (0.06%) contained in Strychnos nux- vomica L. seeds showed considerable change due to artificial inoculation with the spore suspensions of Aspergillus flavus Link: ex. Fries., A. niger van Teigh. and Penicillium citrinum Thorn. recorded as dominant fungal flora on the seeds during storage.